1984
DOI: 10.1097/00132586-198406000-00080
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Physiotherapy for Postoperative Pulmonary Complications

Abstract: A prospective randomized controlled trial was conducted in patients undergoing elective cholecystectomy to assess the value of routine chest physiotherapy. One hundred and two patients entered the study: 47 patients developed no pulmonary complications, 29 had pulmonary atelectasis and a further 26 developed chest infection. The pattern of changes in anerial oxygen tension in the period after operation supponed the Hiniral allocation of the patients. Of 51 patients not receiving physiotherapy, 11 developed ate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…5,21,[29][30][31][32][33] Thus, in view of the susceptibility of this group of patients to the development of postoperative respiratory complications, the indication of physiotherapy before and after the operation is justified, since several studies have confirmed the efficiency of such treatment for reducing pulmonary complications in patients undergoing abdominal surgery. [34][35][36][37] CONCLUSIONS In summary, the present study showed that, among patients undergoing craniotomy, VC and TV are lowered at least up to the fourth postoperative day and VE is lowered up to the second postoperative day. Surgery duration of more than four hours for patients undergoing craniotomy because of aneurysms caused a greater decrease in VC and TV than seen among patients whose surgery lasted for less than four hours.…”
Section: Discussionsupporting
confidence: 54%
“…5,21,[29][30][31][32][33] Thus, in view of the susceptibility of this group of patients to the development of postoperative respiratory complications, the indication of physiotherapy before and after the operation is justified, since several studies have confirmed the efficiency of such treatment for reducing pulmonary complications in patients undergoing abdominal surgery. [34][35][36][37] CONCLUSIONS In summary, the present study showed that, among patients undergoing craniotomy, VC and TV are lowered at least up to the fourth postoperative day and VE is lowered up to the second postoperative day. Surgery duration of more than four hours for patients undergoing craniotomy because of aneurysms caused a greater decrease in VC and TV than seen among patients whose surgery lasted for less than four hours.…”
Section: Discussionsupporting
confidence: 54%
“…Many studies have demonstrated the effectiveness of chest physiotherapy 3,[13][14][15][16][17][18]20,[22][23][24][25][26][27][28][29][30] . However, only a few have had an untreated control group 3,14,[16][17][18] . The present study indicates that chest physiotherapy given to patients before major abdominal surgery effectively reduces the risk of postoperative pulmonary complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical benefit of chest physiotherapy is controversial. In 1954 Thorén 3 reported in a controlled trial that the incidence of pulmonary complications after gallbladder surgery decreased with chest physiotherapy whereas Morran et al 14 concluded in 1983 that chest physiotherapy caused more atelectasis but fewer chest infections. No difference in the rate of pulmonary complications was noted in a study that compared two groups of low-risk patients treated before and/or after operation 15 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 51 patients who received CPT, 18 developed atelectasis and 7 chest infection. The authors concluded that routine prophylactic postoperative CPT significantly reduced the incidence of postoperative chest infection, 80 Torrington et al compared traditional postoperative therapy with and without CPT in a group of 52 morbidly obese subjects following gastric bypass, and concluded that CPT caused patient discomfort, increased hospital cost, and failed to alter the incidence of PPCs. 81 Christensen and colleagues 82 studied 3 postoperative regimens of respiratory therapy on PPCs and lung function in high-risk patients.…”
Section: Chest Physiotherapymentioning
confidence: 99%